PENGARUH KUALITAS AUDIT, KOMPENSASI RUGI FISKAL, DAN PERTUMBUHAN ASET TERHADAP TAX AVOIDANCE - Siti Zulfatin Nihayah; Rachmawati Meita Oktaviani (Jurnal GeoEkonomi, 2022)
This study was made with the aim of knowing the effect of audit quality, fiscal loss compensation, and asset growth on tax avoidance. What is analyzed is the mining sector with 12 samples of mining companies listed on the Indonesia Stock Exchange in the 2016 to 2020 period, using the purposive sampling method, obtained as many as 60 samples after outlier data. The data source used is secondary data which can be obtained officially on the Indonesia Stock Exchange www.idx.co.id. Data analysis uses panel data regression with E-views 12 software. The results of this study indicate that audit quality has no significant effect on tax avoidance, Fiscal loss compensation has a significant positive effect on tax avoidance, and asset growth has a significant negative effect on tax avoidance.